Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.clon.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Geriatric Assessment in Men Aged 70 Years or Older with Localised Prostate Cancer Undergoing Radical Radiotherapy

Abstract: Many older men with localised prostate cancer are vulnerable according to a CGA. The screening tools evaluated were not sufficiently sensitive to identify this group. CGA outcome does not predict for significant acute radiotherapy toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 34 publications
2
33
0
1
Order By: Relevance
“…Secondly, the number of patients in our study who experienced decreased QoL was limited. One study that reported higher levels of comorbidity did find that comorbidity was predictive of impaired long-term QoL after prostate cancer radiotherapy associated with ADT [11]; another, like this study, found no CGA parameter that was predictive for significant radiotherapy toxicity [10]. It is possible that the G8 and CGA tools are poorly-adapted to radiotherapy and localized cancer [12], having been principally developed for chemotherapy or major surgery [13,14].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Secondly, the number of patients in our study who experienced decreased QoL was limited. One study that reported higher levels of comorbidity did find that comorbidity was predictive of impaired long-term QoL after prostate cancer radiotherapy associated with ADT [11]; another, like this study, found no CGA parameter that was predictive for significant radiotherapy toxicity [10]. It is possible that the G8 and CGA tools are poorly-adapted to radiotherapy and localized cancer [12], having been principally developed for chemotherapy or major surgery [13,14].…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, geriatricians usually give importance to the risk of falls as a mark of fragility [13] but fewer than 10% of our patients were found to be at high risk of falling. This suggested that screening tools such as the G8 seem ill-suited to detecting vulnerabilities in this particular population, but even with the fuller CGA used in our study, we failed to predict tolerance of radiotherapy [10]. The development and evaluation of new tools are needed.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Comprehensive Geriatric assessment (CGA) enables precise scoring of daily activities, risk of fall, undernutrition, depression, and comorbidities to help predict whether aggressive cancer treatments will be tolerated. Although CGA is largely used prior to medical interventions, such as chemotherapy [ 14 ] or ADT [ 15 – 17 ], specific studies of older prostate cancer patients undergoing radiotherapy are mostly retrospective, lack precise oncogeriatric evaluation [ 18 – 21 ] or focused on toxicity (assessed by physicians) and not on patient’s related quality of life [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Für andere Fragestellungen beim Prostatakarzinom wie z. B. der Vorhersage von Komplikationen der Strahlentherapie bei älteren Patienten hat sich der G8-Fragebogen bisher nicht als signifikanter prognostischer Faktor erwiesen [14].…”
Section: Diskussionunclassified